The Effect of Culturally Responsive Transformative Teaching (CRTT) on Students’ Science Learning Outcomes - Y., Fitri Amanda Solta; Diliarosta, Skunda; Lestari, Tuti (SEMESTA: Journal of Science Education and Teaching, 2026)
This study was motivated by the low learning outcomes of students in science subjects, which were caused by the difficulty of understanding abstract concepts when using only lecture methods or conventional learning media. The purpose of this study was to determine the effect of the Culturally Responsive Transformative Teaching model on the learning outcomes of eighth-grade students at SMPN 2 Pariaman. This study was a quasi-experimental study with a non-equivalent control group design. The research population consists of all eighth-grade students, with the sample comprising class VIII.1 as the experimental class and VIII.2 as the control class, selected using purposive sampling. The instruments used were multiple-choice questions and student response questionnaires. The questionnaire results showed that students' responses to the use of the Culturally Responsive Transformative Teaching model were very positive, with 98% stating that it was easy to understand. Based on the results of the hypothesis test using the t-test, a significant difference was found between the learning outcomes of students who used the Culturally Responsive Transformative Teaching model and those who did not. Therefore, it can be concluded that the Culturally Responsive Transformative Teaching model has a positive effect on students' learning outcomes in science.